2007
DOI: 10.1136/jcp.2006.039602
|View full text |Cite
|
Sign up to set email alerts
|

Amplification of the HER2 gene in breast cancers testing 2+ weak positive by HercepTest immunohistochemistry: false-positive or false-negative immunohistochemistry?

Abstract: Background: The majority of cases of breast cancer scoring HER2 weak positive (2+) on immunohistochemistry (IHC) using the HercepTest are not associated with amplification of the HER2/neu gene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
23
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 28 publications
4
23
0
Order By: Relevance
“…Unfortunately, only limited FISH data is available in 2+ immunostained specimens. As other have noted [21], disagreement between 2+ overexpression and amplification can occur in up to half of cases. In this study, only 5 of 13 (39%) of the 2+ immunostained specimens were found to have amplification by FISH.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, only limited FISH data is available in 2+ immunostained specimens. As other have noted [21], disagreement between 2+ overexpression and amplification can occur in up to half of cases. In this study, only 5 of 13 (39%) of the 2+ immunostained specimens were found to have amplification by FISH.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that the prognostic significance of moderate HER2 (2C) expression needs to be reevaluated as a predictor for anti-HER2 therapy. Notably, intratumoral heterogeneity of the HER2 gene is a characteristic property of tumors with low and moderate HER2 expression and is associated with decreased DFS (Barrett et al 2007, Seol et al 2012. Therefore, HER2 overexpression without gene amplification should be further evaluated, and the determination of the HER2 status and in particular the predictive value of HER2 (2C) expression should be reconsidered.…”
Section: Discussionmentioning
confidence: 99%
“…2 The unreliability of current HER2 testing methods is illustrated by recent studies showing that some patients who tested negative for HER2 amplification by immunohistochemistry and FISH may still benefit from trastuzumab. 3,4 It has been proposed that this discrepancy is not because of misunderstanding the mechanism of action of the drug, but rather because of the inaccuracy of current testing methods. 5 Currently available FDA-approved FISH assays for the detection of HER2 gene amplification include an assay with a single probe for the HER2 gene and other assays with dual probes, one for the HER2 gene and another for the centromere of chromosome 17 (probe CEP 17, D17Z1).…”
mentioning
confidence: 99%